Peran Teknologi Kecerdasan Buatan (AI) dalam Meningkatkan Efisiensi Proses Belajar dan Pembelajaran - Gleneagles, David Benny; Larasyifa, Firane; Fawaiz, Raihan (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The integration of Artificial Intelligence (AI) technologies in education has attracted significant attention in recent years. This research aims to investigate the role of AI in increasing the efficiency of learning and learning processes. This research examines the current state of AI applications in education, focusing on its impact on the efficiency of learning and learning processes. This research uses the Literature Review method to analyze existing research on AI in education and its impact on learning outcomes. The findings show that AI has the potential to increase the efficiency of learning and learning processes by automating routine tasks, increasing personalized learning, and improving teacher-student interactions. This research concludes that AI can play an important role in increasing the efficiency of the learning and learning process, which can ultimately produce better learning outcomes and higher educational efficiency.